1995
DOI: 10.2307/146190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health on the Work Effort of Single Mothers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press andThe Board of Regents of the University of Wisconsin System are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 15 publications
4
89
1
1
Order By: Relevance
“…[4][5][6][7] Mental illness, alcoholism, drug abuse and poor health have been found to be barriers to employment and earnings in domiciled populations. [8][9][10][11] They are also likely to be important barriers to employment and earnings for homeless populations. For the homeless facing barriers to employment, government programs such as the federal disability programs are an important alternative source of monetary support.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Mental illness, alcoholism, drug abuse and poor health have been found to be barriers to employment and earnings in domiciled populations. [8][9][10][11] They are also likely to be important barriers to employment and earnings for homeless populations. For the homeless facing barriers to employment, government programs such as the federal disability programs are an important alternative source of monetary support.…”
Section: Introductionmentioning
confidence: 99%
“…• Three studies have found evidence supporting the hypothesis that expansions of Medicaid benefits to coverage of former AFDC and other low-income families (without the link to AFDC program participation) increase labor force participation by mothers and decrease AFDC program participation (Moffitt and Wolfe, 1992;Yelowitz, 1995;and Wolfe and Hill, 1995).…”
Section: Evidencementioning
confidence: 97%
“…One such study, conducted using 1984 Survey pf Income and Program Participation (SIPP) data, evaluates the effects of then-proposed welfare reforms on the likelihood of employment of single mothers (Wolfe and Hill, 1995). The authors use a model to simulate policy changes designed to affect the labor force participation of single mothers.…”
mentioning
confidence: 99%
“…The study by Wolfe and Hill (1995), based on the 1994 SIPP, investigates the influence of child and maternal health indicators on different labor market outcomes of female household heads. They find a significant negative effect of mothers' poor health on their market wages, as well as a significant negative effect of problems with activities of daily living (ADL's) on maternal labor force participation.…”
Section: Previous Researchmentioning
confidence: 99%